(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Stati a identità debole e rapporti con le confessioni religiose - 2. Il cratere balcanico - 3. La Bosnia Erzegovina terreno di confronto identitario e di rifiuto dell’autocefalia - 4. Un rapporto sinfonico contestato: il Montenegro - 5. Le denominazioni contese: la Macedonia del Nord - 6. L’Ucraina alla ricerca dell’identità - 7. Autonomia confessionale e autocefalia: per una nuova nozione di territorio canonico. … Is seeking for autocephaly, which is so precious!/ They go in search of autocephaly- so precious! / Of autocephalous they journey: how dear it is! ABSTRACT: The "Weak States" of the Balkans born from the dissolution of Yugoslavia and the USSR seek legitimacy and struggle to strengthen their national identity. This is currently happening through the recognition of autocephaly to their Orthodox Churches in order to build on the symphonic and stable relationship between State and Churches. The article analyzes the status of relations between the state entities of Kosovo, Bosnia and Herzegovina, Montenegro, Macedonia and Ukraine. In this perspective, the conflict between different religious designations claiming to be represented as identity representations before the State is highlighted. Additionally, the conflicts within the Orthodox pae granting the tomos to recognize autocephaly are explored.